THE RELATIONSHIP BETWEEN GUT MICROBIOME ALTERATIONS AND HEPATOCELLULAR CARCINOMA DEVELOPMENT IN CHRONIC HEPATITIS B PATIENTS: A CLINICAL AND MICROBIOLOGICAL STUDY FROM IRAQ - Obeed, Ameer Najy (PT. Antis International Publisher, 2025)
Objective: To investigate the relationship between gut microbiome composition and the development of HCC in Iraqi patients with chronic HBV infection. Method: A cross-sectional case-control study was conducted involving 150 participants divided into three groups: HBV with HCC (n=60), HBV without HCC (n=60), and healthy controls (n=30). Clinical, biochemical, and microbiome data (16S rRNA sequencing of fecal samples) were collected. Statistical analyses included ANOVA, chi-square, and Pearson correlation. Results: Patients with HCC exhibited significant dysbiosis, characterized by decreased microbial diversity (Shannon index: 2.8 ± 0.4) compared to HBV-only (3.6 ± 0.5) and controls (4.1 ± 0.3), p<0.001. Increased abundance of Bacteroides fragilis and Enterobacteriaceae correlated with higher AFP levels (r=0.63, p<0.001). Novelty: Gut microbiome alterations are associated with HCC development in chronic HBV patients. These findings suggest potential microbiome-based biomarkers for early detection and therapeutic strategies.